Mapping Research on Fashion Marketing Using Biblioshiny- R (2014-2024) - Nisrina Nur Ismail; Lina Nurjanah (Institut Manajemen Wiyata Indonesia & Asosiasi Peneliti Manajemen Indonesia, 2024)
Purpose: Scholars have been actively exploring various aspects of fashion marketing framework, with a focus on delineating the characteristics and trends of keywords, authors, journals, and citations. This review aims to analyze existing literature to identify key issues, models, solution approaches, and potential future directions in this field. Design/methodology/approach: Our approach utilizes a dataset comprising 195 articles on fashion marketing research sourced from Scopus. Employing a combination of statistical, bibliometric, and analytical techniques, we systematically examine how the literature addresses these themes. Data analysis is conducted using biblioshiny and VOSviewer software to generate bibliometric maps of research advancements in fashion marketing. Findings: The findings reveal that research developments in this domain are visually represented through six clusters. Cluster one encompasses 12 topics, cluster two includes 7 topics, cluster three comprises 5 topics, cluster four entails 5 topics, cluster five encompasses 4 topics, and cluster six consists of 4 topics. This research endeavors to assess the evolution and trajectory of fashion marketing maps as documented in Scopus-indexed journals. The dataset under scrutiny comprises 195 publications, and the ensuing export data is meticulously processed and analyzed utilizing the R Bibliometrix application program. The objective is to delineate the bibliometric map of fashion marketing research development. The findings reveal a noteworthy surge in the number of publications focusing on fashion marketing. Notably, the Journal of Global Fashion Marketing and Management emerges as the predominant journal, with Ko E. being the most prolific author, and a substantial proportion of citations originating from works authored by Kong HM (2021). The prevalent themes identified through keyword analysis encompass consumer behavior, consumption behavior, sustainability, and fashion industry, fashion industry, consumption behavior, and strategic planning. In terms of conceptual structure, the research employs thematic maps to visually represent the distribution of themes and sub-themes across four clusters: dropping or emerging themes, basic themes, highly developed and isolated themes, and motor themes. The resulting conceptual framework not only sheds light on the current landscape but also serves as a catalyst for ongoing research in this burgeoning field. This comprehensive understanding stands to benefit academics, researchers, and practitioners on a global scale. Research limitations/implications: This study is restricted to articles discussing the fashion marketing framework.